Enhancement of hepatic autophagy increases ureagenesis and protects against hyperammonemia - Soria, Leandro R. (Proc Natl Acad Sci U S A, 2018)
Ammonia is a potent neurotoxin that is detoxified mainly by the urea cycle in the liver. Hyperammonemia is a common complication of a wide variety of both inherited and acquired liver diseases. If not treated early and thoroughly, it results in encephalopathy and death. Here, we found that hepatic autophagy is critically involved in systemic ammonia homeostasis by providing key urea-cycle intermediates and ATP. Hepatic autophagy is triggered in vivo by hyperammonemia through an α-ketoglutarate–dependent inhibition of the mammalian target of rapamycin complex 1, and deficiency of autophagy impairs ammonia detoxification. In contrast, autophagy enhancement by means of hepatic gene transfer of the master regulator of autophagy transcription factor EB or treatments with the autophagy enhancers rapamycin and Tat-Beclin-1 increased ureagenesis and protected against hyperammonemia in a variety of acute and chronic hyperammonemia animal models, including acute liver failure and ornithine transcarbamylase deficiency, the most frequent urea-cycle disorder. In conclusion, hepatic autophagy is an important mechanism for ammonia detoxification because of its support of urea synthesis, and its enhancement has potential for therapy of both primary and secondary causes of hyperammonemia.